Cost-effectiveness analysis of rotavirus vaccination in China: Projected possibility of scale-up from the current domestic option - Shuhui Cui; Ruoyan Gai Tobe; Xiuting Mo; Xiaoyan Liu; Lingzhong Xu; Shixue Li (BMC Infectious Diseases, 2016)
Abstract Background Rotavirus infection causes considerable disease burden of acute gastroenteritis (AGE) hospitalization and death among children less than 5 years in China. Although two rotavirus vaccines (Rotarix and RotaTeq) have been licensed in more than 100 countries in the world, the Lanzhou Lamb rotavirus vaccine (LLR) is the only vaccine licensed in China. This study aims to forecast the potential impacts of the two international vaccines compared to domestic LLR. Methods An economic evaluation was performed using a Markov simulation model. We compared costs at the societal aspect and health impacts with and without a vaccination program by LLR, Rotarix or RotaTeq. Parameters including demographic, epidemiological data, costs and efficacy of vaccines were obtained from literature review. The model incorporated the impact of vaccination on reduction of incidence of rotavirus infection and severity of AGE indicated by hospitalization, inpatient visits and deaths. Outcomes are presented in terms of quality-adjusted life years (QALYs) gained and incremental cost-effectiveness ratio (ICER) compared to status quo. Results In a hypothetical cohort of 100,000 infants, the two international vaccines showed very good cost-effectiveness, with ICER of Rotateq and Rotarix shifting from LLR of $1715.11/QALY and $2105.66/QALY, respectively. Rotateq and Rotarix had significantly decreased incidence compared to LLR, particularly among infants aged 6 months to 2 years. Conclusions RotaTeq is expected to introduce in the national routine immunization program to reduce disease burden of rotavirus infection with universal coverage.